A collaborative framework for multiagent systems - Ahmed M.; Ahmad M.S.; Yusoff M.Z.M. (2023)
In this paper, we demonstrate the use of agents to extend the role of humans in a collaborative work process. The extended roles of agents provide a convenient means for humans to delegate mundane tasks to software agents. The framework employs the FIPA ACL communication protocol which implements communication between agents. An interface for each agent implements the communication between human actors and agents. Such interface and the subsequent communication performed by agents and between agents contribute to the achievement of shared goals. 2010 Springer-Verlag Berlin Heidelberg.